Schools, curriculum and civic education for building democratic citizens - Print, Murray; Lange, Dirk, 1964- (Civic and political education ;, 2012)
How can schools and the school curriculum contribute to building democratic citizens? This is a major question posed by governments, educational systems, schools, teachers and researchers around the world. One important way is to identify the competences needed for preparing democratic citizens and incorporate these within both the formal and informal school curriculum. Another question must then be posed- what competences do young citizens need to be considered as active and engaged in modern democracies? In 2011 an invited research symposium of leading civic and political educators, and social scientists from across Europe met in Hannover, Germany to consider this key concern facing Europe today. In examining the above questions the symposium addressed two significant issues: 1. Identify key competencies required for active citizenship of young people in Europe of the future. 2. Translate those competencies to school-based activities in the form of curricular and pedagogical strategies. The publication Civic Education and Competences for Engaging Citizens in Democracies addressed the first issue and this volume addresses the second issue. Through discussion in the invited symposium, previously prepared papers, and participation in a modified Delphi Technique the participants have prepared chapters for this book. The chapters of this book represent the contribution of the participants before, during and after the symposium with opportunities for review and reflection about competences for democratic citizenship and the role of schools and the curriculum. Murray Print and Dirk Lange are professors from the University of Sydney and Leibniz University of Hannover respectively and are national leaders in civics and citizenship education in their respective countries. They have brought together a group of leading European civic and citizenship educators from different academic fields to explore the key issue and to identify the competences for young people to become active and engaged European citizens.